The Role Of Some Innovative Technologies In Teaching Chemistry In Secondary School - Ruziyev I.Kh.; Ne'matova D.G.; Imomova M.S.; Ne'matova D.G. (Peerian Journals Publishing, 2024)
Introducing innovative methods into the educational process at work, ensuring the coordination of educational programs with production, teachers using many innovative technologies in learning the cycle of natural and scientific sciences, and using these technologies in all types of classes.In addition, there are forms of working with students to equalize their knowledge level
Keywords: information; innovation; technology; communication